2014
DOI: 10.5194/se-5-1011-2014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of high-velocity lower crust on the South Atlantic rifted margins and implications for the interplay of magmatism and tectonics in continental breakup

Abstract: Abstract. High-velocity lower crust (HVLC) and seawarddipping reflector (SDR) sequences are typical features of volcanic rifted margins. However, the nature and origin of HVLC is under discussion. Here we provide a comprehensive analysis of deep crustal structures in the southern segment of the South Atlantic and an assessment of HVLC along the margins. Two new seismic refraction lines off South America fill a gap in the data coverage and together with five existing velocity models allow for a detailed investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 70 publications
3
24
0
Order By: Relevance
“…Instead, the combination of a preexisting plume and rifting could form SDRs, as seems clear for the cases of the Iceland (27) and Reunion/ Deccan plumes (28). This scenario is consistent with the observation that rifting along the southern South Atlantic margins appears to start with an early magma-poor rift stage, and evolves to a magma-rich breakup stage (29), an observation inconsistent with straightforward interpretations of a plume-head source for the creation of SDRs (e.g., ref. 5).…”
Section: Discussionsupporting
confidence: 81%
“…Instead, the combination of a preexisting plume and rifting could form SDRs, as seems clear for the cases of the Iceland (27) and Reunion/ Deccan plumes (28). This scenario is consistent with the observation that rifting along the southern South Atlantic margins appears to start with an early magma-poor rift stage, and evolves to a magma-rich breakup stage (29), an observation inconsistent with straightforward interpretations of a plume-head source for the creation of SDRs (e.g., ref. 5).…”
Section: Discussionsupporting
confidence: 81%
“…The break‐up unconformity (dark green in Figures b and c), merges with the top of the SDR wedges to suggest that the SDR formed before seafloor spreading. The earliest oceanic crust is interpreted immediately seaward of the SDRs [ Koopmann et al ., ; Franke et al ., ; Becker et al ., ]. The postrift sediments on the South American margin reveal a thickness of 3.5 km at the seaward end of the SDRs, which thins to 2.5 km at the feather edge.…”
Section: Resultsmentioning
confidence: 99%
“…The HVLC body is asymmetric, with a much greater cross‐sectional area on the South African margin, as discussed by Becker et al . []. It remains an open question, to what an amount of continental crust is found below the SDRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through such studies globally, the large-scale structure of a rift system has been studied by numerous previous workers (Chian et al, 1995;Pichot et al, 2014;Kvarven et al, 2015;Peace et al, 2016). Such studies are useful because they reveal broad characteristics of rifting (Becker et al, 2014), such as rift asymmetry (Lister et al, 1986). These studies have shown that asymmetric rifts are common, with implications for exploration since structure, heat flow and thus hydrocarbon prospectivity vary between conjugate margins (Peace et al, 2016).…”
Section: Why Are Conjugate Margin Studies Useful?mentioning
confidence: 99%